2017
DOI: 10.1017/s0954579417001468
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity moderates the influence of proximal episodic stress on the cortisol awakening response and depressive symptoms in adolescents

Abstract: Childhood adversity (CA) is known to predict sensitization to proximal stressors. Researchers have suggested that disruptions in hypothalamus-pituitaryadrenal axis functioning may be a biological mechanism. If so, CA may predict altered associations between proximal life stress and markers of cortisol secretion. We examined whether CA moderates associations between recent episodic stress and (a) the cortisol awakening response (CAR), and (b) depressive symptoms, in 241 adolescents aged 14-17 years (cortisol n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 138 publications
(186 reference statements)
1
20
0
Order By: Relevance
“…As a preliminary step, we tested for population stratification effects (i.e., confounding effects that occur when race is correlated with outcomes of interest and specific genotypes). As reported elsewhere (for full details, see Starr et al, 2017), in the current sample, non-Caucasian youth had higher MGPS than did Caucasian youth, t (239) = 2.10, p = .036, and race moderated the association between MGPS and depressive symptoms. Race was also marginally associated with ICA, t (239) = 1.68, p = .094; scores were higher for non-White adolescents.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…As a preliminary step, we tested for population stratification effects (i.e., confounding effects that occur when race is correlated with outcomes of interest and specific genotypes). As reported elsewhere (for full details, see Starr et al, 2017), in the current sample, non-Caucasian youth had higher MGPS than did Caucasian youth, t (239) = 2.10, p = .036, and race moderated the association between MGPS and depressive symptoms. Race was also marginally associated with ICA, t (239) = 1.68, p = .094; scores were higher for non-White adolescents.…”
Section: Resultssupporting
confidence: 78%
“…Youth were recruited to participate from the community of a mid-sized metropolitan area. Families were recruited using a range of recruitment methods, including online and community advertisements (50.6% of families), a commercial mailing list of families with potentially age-eligible children (40.2%), and ResearchMatch (4.1%), an online clinical research registry (additional recruitment details are included in Starr et al, 2017). Participants were excluded from study participation if they had a major physical, neurological, or pervasive developmental disorder, a prior diagnosis of any bipolar or psychotic disorders, English language difficulties, or previous participation of siblings or any other household member.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study that carefully dated both the occurrence of different stressful life events and youths' development of depression, for example, interpersonal life events were found to be statistically unique predictors of subsequent onset of MDD across two adolescent samples; in contrast, noninterpersonal events were unrelated to depression (Vrshek-Schallhorn et al, 2015). In a second longitudinal study, exposure to interpersonal life events interacted with a multilocus genetic profile score to prospectively predict increases in depressive symptoms in adolescents but, again, these effects were specific to interpersonal stressors (Feurer et al, 2017; see also Starr et al, 2017;Starr, Dienes, Li, & Shaw, 2019). Finally, a third study found that interpersonal life events involving targeted rejection precipitated onset of depression three times faster than other types of major life events (Slavich, Thornton, Torres, Monroe, & Gotlib, 2009; see also Massing-Schaffer et al, 2019).…”
Section: Interpersonal Life Stress and Depressionmentioning
confidence: 88%
“…One reason for this difference may be that early adversity is often conceptualized as childhood‐ specific stressors, such as childhood maltreatment (e.g., Carpenter et al, ), or all stressors occurring prior to age 13 or 15, whereas the STRAIN considers early adversity as all stressors experienced prior to 18 years of age. Alternatively, it is possible that early adversity may interact with recent stressors to modulate HPA axis function (e.g., Starr et al, ).…”
Section: Discussionmentioning
confidence: 99%